Little hope for the polyploid endemic Pyrenean Larkspur (Delphinium montanum): Evidences from population genomics and Ecological Niche Modeling. Issue 3 (18th March 2022) - Salvado, Pascaline; Aymerich Boixader, Pere; Parera, Josep; Vila Bonfill, Albert; Martin, Maria; Quélennec, Céline; Lewin, Jean‐Marc; Delorme‐Hinoux, Valérie; Bertrand, Joris A. M.
Abstract: Species endemic to restricted geographical ranges represent a particular conservation issue, be it for their heritage interest. In a context of global change, this is particularly the case for plants which belong to high‐mountain ecosystems and, because of their ecological requirements, are doomed to survive or disappear on their "sky islands". The Pyrenean Larkspur ( Delphinium montanum, Ranunculaceae) is endemic to the Eastern part of the Pyrenees (France and Spain). It is now only observable at a dozen of localities and some populations show signs of decline, such as a recurrent lack of flowering. Implementing population genomics approach (e.g., RAD‐seq like) is particularly useful to understand genomic patterns of diversity and differentiation in order to provide recommendations in term of conservation. However, it remains challenging for species such as D .  montanum that are autotetraploid with a large genome size (1C‐value >10 pg) as most methods currently available were developed for diploid species. A Bayesian framework able to call genotypes with uncertainty allowed us to assess genetic diversity and population structure in this system. Our results show evidence for inbreeding (mean G IS  = 0.361) within all the populations and substantial population structure (mean G ST  = 0.403) at the metapopulation level. In addition to a lack of connectivity between populations, spatial projections of Ecological Niche Modeling (ENM) analyses under different climatic scenarios predict a dramatic decrease of suitable habitat for D .  montanum in the future. Based on these results, we discuss the relevance and feasibility of different conservation measures. Abstract : We used a population genomics and Ecological Niche Modeling approach to infer the conservation status of the endemic and vulnerable Pyrenean Larkspur (Renonculaceae). Populations display low levels of genetic diversity as well as strong population structure. ENM approach predict a dramatic decrease of the availability of the habitat of the species in the future.